Kulturlivets etnografi - Arvidsson, Alf (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2013)
This article proposes intensified studies in “culture life” or “the Arts” by way of an ethnography inspired by Howard Becker’s model of Art Worlds and focusing on how, where and by whom arts are made. This includes the situation where artists, brokers, audiences and critics meet but also the inclusion in criticism, academic education and art grants systems. A focus on situations would take notice of how the premises and present actors in the situation put limitations on but also can be seen as productive forces making art works possible and affecting their formal structures. Furthermore, a comparative perspective on how arts using different media and affecting different senses are put on equal standing within a “high culture” concept is important in order to grasp the position of the arts in society today.